Hubungan Aktivitas Pendakian Gunung Dengan Kecakapan Hidup Mahasiswa - Yedi Abdul Hadi Sugandi; Asep Ramdan Afriyuandi; Andi Kurniawan Pratama (Jurnal Sporta Saintika, 2025)
Mountaineering is not just a challenging physical activity, but also a journey that enriches one's life skills. Through climbing, we learn about resilience, cooperation, and the ability to face obstacles, all of which are essential in navigating our daily lives. The purpose of this study is to determine and analyze the relationship between mountaineering activities and life skills. This research uses a quantitative approach with a correlational method. It includes research type and methodology, population and sample, data collection methods, research tools, and data analysis methods. The results of this study are about the relationship between life skills and mountaineering. The data collected come from the results of a questionnaire that has been analyzed systematically. It begins with a description of the respondent's data, then the measurement results for each variable, and is then analyzed to determine the level of correlation between the two.